2015
DOI: 10.4103/2277-9175.151574
|View full text |Cite
|
Sign up to set email alerts
|

The value of transcranial Doppler derived pulsatility index for diagnosing cerebral small-vessel disease

Abstract: Background:The pulsatility index (PI), measured by transcranial Doppler (TCD) ultrasonography, can reflect vascular resistance induced by cerebral small-vessel disease (SVD). We evaluated the value of TCD-derived PI for diagnosing SVD as compared with magnetic resonance imaging (MRI).Materials and Methods:Fifty-six consecutive cases with SVD (based on MRI) and 48 controls with normal MRI underwent TCD. Based on MRI findings, patients were categorized into five subgroups of preventricular hyperintensity (PVH), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 20 publications
1
37
0
Order By: Relevance
“…First, apart from an ICP elevation, many factors affect MCA PI‐induced CVR changes. For example, Ghorbani et al showed that the MCA PI was associated with cerebral small‐vessel disease. Stretti et al found that body temperature affected cerebral hemodynamics; an elevated temperature induced cerebrovascular relaxation associated with a reduced CVR but an increased ICP attributable to cerebral hyperemia.…”
Section: Discussionmentioning
confidence: 99%
“…First, apart from an ICP elevation, many factors affect MCA PI‐induced CVR changes. For example, Ghorbani et al showed that the MCA PI was associated with cerebral small‐vessel disease. Stretti et al found that body temperature affected cerebral hemodynamics; an elevated temperature induced cerebrovascular relaxation associated with a reduced CVR but an increased ICP attributable to cerebral hyperemia.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to determine whether the same findings would be observed in other ethnic populations. In addition, studies investigating the value of transcranial Doppler examination in the diagnosis of intracranial carotid artery stenosis 28,29 and guidance of α-blocker therapy are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TCD ultrasound can effectively assess the cerebral blood flow velocity of intracranial blood vessels in patients with sickle cell disease, stroke or brain death 14 . The pulsatility index, a parameter of TCD ultrasound, has been used for many years to reflect the resistance of small vessels 15,16,17 . This study aimed to investigate the relationship between the pulsatility index in TCD ultrasound and cerebral small vessel disease in elderly patients.…”
Section: Introductionmentioning
confidence: 99%